Spinal trauma - Ellis, Jim (Curr Rev Musculoskelet Med, 2014)
The practice of spinal immobilization has existed since the 1960s under the premise that trauma victims with cervical spine injuries may suffer neurologic injury if moved without stabilization consisting of a rigid cervical collar and long spine board. Because of this assumption, it is of particular importance to assess for movement of the cervical spine with and without spinal immobilization. Over time, the on-field management of athletes with a mechanism consistent with spinal cord injury (SCI) has evolved and produced protocols that can be considered standard of care. Attempts to find evidencebased research to verify the necessity of a rigid collar and long spine board as the only option in athletic medicine for suspected SCI is difficult. As changes occur in the Emergency Medical Services standards, there will be opportunities to see how their processes relate to athletes and the rationale for immobilization on the field of play. Going forward, there could very well be a significant change in the approach to and management of the athlete down on the field of play with a suspected spinal cord injury.